Cloud Computing Technology in Supporting the Implementation of One Data Indonesia - Sawitri, Dara (Universitas Trilogi, 2024)
Cloud computing services provide resources in the form of infrastructure platforms, software, and other hosting to customers. Data provided by digital systems is carried out in a cloud computing model service, providing data access anywhere as long as it is connected to the internet. In today's digital era, cloud computing supports the implementation of One Data Indonesia (SDI) to obtain quality data that is well integrated between local governments and the central government. With One Data Indonesia, it is hoped that data will have consistency so that it can be relied on for analysis and has a good level of security. One Data Indonesia is an idea from the Indonesian government to combine and maximize the use of data generated by government agencies in Indonesia so that it is useful for decision-making, planning, and more optimal public services. In realizing SDI, cloud computing can be utilized for data storage, ease of access, and creating better cooperation between government agencies. Cloud computing can help the Indonesian government optimize public services safely, and reliably, and maximize data potential in various fields to gain competitive advantages in all sectors of government.